Knowledge within the intellectual tradition of Islam - Farooqui, Jamil (Bangladesh Institute of Islamic Thought, 2017)
Knowledge has been misconceived and is equated with information. This study, based upon primary sources, explains that knowledge from the ideational system of Islam is the consciousness of high order of reality and truth lying behind the signs spread throughout the working of the universe. Knowledge is the identification and realization of the Highest Reality, its magnificence and power and submission to His will. In the context of the physical objects, it makes humans aware of the origin, structure and the function which an object performs and how it can be used for the comfort and benefit of humanity. Hearing, sight and heart are the significant means of acquiring knowledge. If one applies them in an appropriate way and goes through the process of tawassum (ability to understand the signs of nature) to tadhakkur (remembrance” of God), one acquires the knowledge closer to reality. There are three levels of knowledge according to the degree of certainty: knowledge by reference (‘ilm al-yaqÊn), knowledge by perception (‘ain al-yaqÊn) and knowledge by intuition (Íaqqa al-yaqÊn).